AN EMPIRICAL STUDY OF THE GLASS INDUSTRY’S CORE VALUES AND ITS IMPACT ON THE SAFETY OF WORKERS WITH SPECIAL REFERENCE OF SAFETY TOOLS - Porwal, Shalu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper explored the need for safety measures and safety tools for worker’s life balance from the perspective of glass industries core values. Safety plays a significant part in the balancing of workers’ lives & safety tools are the weapons to win the hassle-free journey of production. The hassle-free workable area is the right of every worker, which enhances their life span and empowers them to be a part of qualitative products and services. Working people’s worth and values represent industrial core values. These core values are the base of industrial goodwill, growth, and mouth-to-mouth brand promotion. Satisfied workers are themselves the conveyors of their industry’s goodwill. They play that critical part that the poster, banner, brochure, or any other mode of brand promotion never played. As per the Cambridge Dictionary, “a core value is a value or belief that is more important than any other.” Industrial work with core values gives a sensible approach in terms of long-term success goals. The better the core values, the more chances you have to get success in the long term.